2022
DOI: 10.3390/en15031090
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Mode Observer-Based Fault Detection in Continuous Time Linear Switched Systems

Abstract: This paper studies the problem of fault detection for continuous time linear switched systems in the presence of disturbance. For this purpose, a fault detection sliding mode observer approach is designed to generate the residual signal. To minimize the effect of disturbance from the residual, the problem is formulated into H∞ filtering technique to increase more robustness. To deal with the issue of the switched systems stability, the Lyapunov-Krasovskii functional method is utilized along with average dwell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…One can take z 2 as given in (17), and its derivative is described in (18), where again the second derivative of the desired voltage is included simply to have an equation that may consider this voltage as variable.…”
Section: Case a Given In [4]mentioning
confidence: 99%
See 1 more Smart Citation
“…One can take z 2 as given in (17), and its derivative is described in (18), where again the second derivative of the desired voltage is included simply to have an equation that may consider this voltage as variable.…”
Section: Case a Given In [4]mentioning
confidence: 99%
“…These problems can be mitigated by applying non-linear control methods, which improve transient response. Some of the currently applied non-linear control methods are, for example, optimal control [3], model predictive control (MPC) [1], neuronal network, extended state observer based control [8], fuzzy logic control (FLC) [7,9], passivity-based control [12], sliding mode control (SMC) [16], twisting based SMC [6,11] and sliding mode observer [17]. In this paper, it is shown that the DC-DC buck converter is highly effective for DC voltage regulation, and the desired voltage output is ensured by implementing an SMC considering three different cases of the control law.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the problem of Fault Diagnosis and Identification has attracted more and more attention in both industry and academic communities due to the increasing demand for safety and reliability in a wider engineering application and several research papers on this subject have been published. [12][13][14][15][16][17][18][19][20]. For example, in [12] a robust state estimation and actuator fault detection has been developed for a class of uncertain switched systems using the Average Dwell Time (ADT) concept.…”
Section: Introductionmentioning
confidence: 99%
“…In [19], the adaptive actuator and sensor fault estimation observer issue has been investigated for continuous-time switched systems despite the measurement disturbances. A robust sliding mode observer-based fault detection for a boost converter was considered in [20] by using the ADT concept with respect H ∞ performance index to minimize disturbance effect from residual signal and a Lyapunov functional technique is also used for switched systems stability.…”
Section: Introductionmentioning
confidence: 99%